Analisis Kinerja Layanan Angkutan Umum Mikrotrans JakLingko Trayek Jak 34 Ditinjau dari Standar Pelayanan Minimal dan Kepuasan Pelanggan di Wilayah Jakarta Timur - Zashika, Sulthon Makruf (Jurnal Sistem Transportasi & Logistik, 2022)
The purpose of this study is to change the stigma that exists in the community that service performance on small bus public transportation is not always the same. JakLingko has regulations regarding the minimum service provided to customers. This research uses Multiple Linear Regression Analysis and Importance Performance Analysis (IPA) analysis. The results of the Multiple Linear Analysis show that there is a positive influence between the variables of SPM (Minimum Service Standards) and Customer Satisfaction on the Performance of JakLingko Microtrans public transportation services. The results of the customer's IPA analysis assessed that the JakLingko Microtrans transportation unit was always clean and tidy. In addition, the results of customer assessments show that the operation of the JakLingko Mikrotrans is in accordance with the route and the transportation unit did not broke down during the trip. With Jak Lingko Mikrotrans, the public transportation system in Jakarta has become more inclusive of areas that are not reached by existing public transportation.